The self reported psychosocial wellbeing of adolescent childhood cancer survivors in New Zealand - Yallop, Kathy (Auckland University of Technology, 2011)
There has been increased recognition of the psychosocial impact of a diagnosis of cancer as well as the intensive treatment necessary to effect a cure. However there is a lack of consensus across studies on the degree and type of psychosocial difficulties experienced by young survivors. The aim of this study was to describe the self-reported psychosocial wellbeing of adolescent childhood cancer survivors. In this case-control study, 170 childhood cancer survivors aged 12 to 18 years completed an internet based survey. This was a modified version of the Youth'07 Health and Wellbeing Survey of Secondary School Students in New Zealand. The comparison group were the 9,107 students who took part in the Youth'07 survey. Psychosocial wellbeing was assessed by four standardised measures of: a) wellbeing (WHO-5), b) anxiety (MASC-10), c) depression (RADS2-SF) and d) emotional and behavioural difficulties (SDQ). The majority of childhood cancer survivors scored within the normal range across all four measures; WHO-5 (89%), MASC-10 (93%), RADS2-SF (94%) and SDQ total difficulties (82%). Compared to a normative sample of their peers, they reported greater psychosocial wellbeing (very good or excellent 60.2% vs. 49.9%, p <0.01), greater prosocial behaviour (86.5% vs. 78.2%, p<.01) and a trend towards less depression (6.1% vs. 10.6%, p=.09). There was however, a small but important minority who reported significant depression (9%), anxiety (7%), poor emotional wellbeing (11%) and increased emotional and behavioural difficulties (18%). Survivors of CNS disease, older age and older age at diagnosis were shown to have the greatest psychosocial difficulties. Following a diagnosis of childhood cancer, intensive therapy and the subsequent risk of adverse health outcomes, one might expect childhood cancer survivors as a group to not be doing as well as their peers in terms of psychosocial wellbeing. The findings of this study, however, show that childhood cancer survivors are doing as well, and in some cases better, than their peers. This is the first study to report on the psychosocial wellbeing of adolescent childhood cancer survivors within New Zealand.